Ecological status of the Umban Sari River waters in Pekanbaru City with macrozoobenthos bioindicators using the ABC curve method - Luhlu Aprilia Helmi; Yuliati; Eko Prianto (JURNAL MINA SAINS, 2025)
Rivers are surface water flows from upstream to downstream estuaries. The Umban Sari River is a tributary that flows into the Siak River. The activities along the river provide ecological pressure that continues to accumulate downstream. This study was conducted in March-May 2024 using macrobenthos as bioindicators of pollution. The purpose of this study was to determine the abundance, diversity, uniformity, dominance, biomass and ecological status of the Umban Sari River waters based on the ABC (Abundance and Biomass Comparison) macrobenthos curve method. This research uses a survey method by determining sampling stations using purposive sampling consisting of three stations. Macrozoobenthos sampling was carried out 3 times with an interval of once a month (30 Day interval). The results showed that the found 8 macrozoobenthic species consisting of Pila ampullacea, Pomacea canaliculate, Lymnaea rubiginosa, Bellamya sumatrensis, Gyraulus convexiusculus, Indoplanorbis exestus, Melanoides pantherine and Schistosoma sp. The highest abundance of macrozoobenthos was found at station I upstream of the river with an average of 3,685 ind/m2 and the lowest was found at station III downstream of the river with an average of 2,148 ind/m2. The diversity and uniformity of the macrozoobenthos is in the medium category, there are no species that dominate. The highest macrozoobenthic biomass was found at station I upstream of the river with an average of 2,643 gr/m2 and the lowest was found at station III downstream with an average of 2,199 gr/m2. The K-Dominant Hypothesis of the ABC curve in the Umban Sari River is included in the category and condition of an undisturbed and unpolluted ecosystem. However, the dominance of the relative biomass (BR) line was found to be only slightly above the relative abundance (KR) line and was close to overlapping, this indicates that the ecosystem condition is starting to become polluted.